The Urgency of Developing a Crewing Management System (CMS) for PT MCS Internasional in the Era of Maritime Digitalization - Indah Purnaningratri; Raden Novi Andri Setiawan; Endah Nur Widhianingsih; Hendra Purnomo; Susiarni Magdalena (Pelopor Publikasi Akademika, 2025)
The maritime industry is undergoing a rapid digital transformation that is reshaping traditional operations and human resource management. PT MCS Internasional, a large-scale maritime service provider managing crew operations for multiple types of vessels and companies, faces challenges in data management, efficiency, and compliance monitoring. The complexity of handling numerous crew members and diverse client requirements demands a structured digital solution. This research aims to examine the necessity and urgency of developing a Crewing Management System (CMS) tailored to PT MCS Internasional’s operational framework. Using a qualitative descriptive method through interviews, observation, and document analysis, the study finds that the manual and semi-digital processes currently in use result in data duplication, low accuracy, and slow decision-making. Customized CMS is essential to streamline operations, integrate multiple data sources, ensure regulatory compliance, and improve competitiveness. The paper concludes that implementing a comprehensive CMS will serve as a strategic move to enhance efficiency, reliability, and scalability in managing maritime human resources.